Evaluation of stress distribution in coronal base and restorative materials: A narrative review of finite element analysis studies - Polat, Yelda; Yavuz, İzzet (Conservative Dentistry Journal, 2024)
Background: Analyzing the stresses created by functional and parafunctional forces on teeth, bones, soft tissues, and intraoral dental materials is crucial for enhancing the success and development of restorations. Purpose: The purpose of this review is to evaluate studies that examine stress distribution in coronal base and restorative materials using the method of finite element analysis. Review: The three-dimensional finite element analysis method is extensively utilized to study biomechanical behavior and assess stress distribution within dental materials. Numerous studies from 2010 to 2024 have investigated the stress caused by polymerization shrinkage and the distribution of stress in various base and restorative materials. Conclusion: This review emphasizes findings related to stress distribution in coronal base and restorative materials, stressing the importance of considering the elastic modulus and thickness of base materials, and highlighting the need for additional research in this field.